FEEDING JEJUNOSTOMY AS A LIFELINE FOR ESOPHAGEAL MALIGNANCIES: Feeding Jejunostomy - Zafar, Usama; Majeed, Farhan Ahmed; Hanif, Abuzer; Ali, Ahmad; Imtiaz, Tashfeen (Pakistan Armed Forces Medical Journal, 2018)
Objective: To share experience about enteral nutrition via feeding jejunostomy in patients undergoingesophagectomies or for palliative purposes and compare our findings with similar studies. The objective of thisstudy is to show the safety/viability of the procedure in patients undergoing esophagectomies and as a palliativeprocedure in inoperable CA esophagus.Study Design: Observational study.Place and Duration of Study: CMH Lahore and CMH Rawalpindi, from 2010 to 2016.Material and Methods: Feeding jejunostomy is a surgical technique for placement of a feeding tube into smallintestine mainly for administration of nutrition. Our method was based upon Witzel jejunostomy techniquewith emphasis on early postoperative commencement of enteral nutrition & achievement of target caloric andprotein requirement subsequently. A total of 439 patients who underwent feeding jejunostomy were included.These include patients suffering from any benign or malignant pathology for which esophagectomy was doneand those patients who are suffering from inoperable carcinoma and underwent feeding jejunostomy forpalliative purposes.Results: Result and price analysis shows that feeding jejunostomy is financially viable as per day nutrition costfor feeding via total parenteral nutrition (TPN) is Rs 8500 ± 500 (including required daily labs) and for enteral itsaround 560 ± 40 Rs/day. None of our patient was put on TPN and none suffered from malnutrition. Percentage ofcomplications rendered were on par with the results from similar studies and meta-analysis.Conclusion: We conclude that feeding jejunostomy is financially viable with minimal complications, that justifiesits use and its superiority over TPN.